PERANAN KEPALA SEKOLAH SEBAGAI MANAJER DI TAMAN KANAK-KANAK SE-KECAMATAN TAMPAN KOTA PEKANBARU - Eva Eriani; Wusono Indarto; Yeni Solfiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrck: The aim of this research is to know the roles of the principal as manager in kindergarten in District of Tampan in Pekanbaru. The population and sample of this research are all of the principals of kindergartens which the total of them is 50 persons. The technique of data collection used questionnaires in likert scale. The technique of data analysis used statistical method by using SPSS for Windows Ver.16 program. The data analysis used percentage form, the research result of percentage to the roles of the principals as manager in kindergarten in District of Tampan in Pekanbaru shows that 59.7% in an enough category level. Meanwhile, if viewed from each indicators; the indicator of planshows 66.3% in a good category level, the indicator of organize shows 55% in an enough category level, the indicator of lead shows 59.6% in an enough category level, and the indicator of control shows 56.8% in an enough category level.Key Words: Principal, Manager